The Role of Behavioral Factors in Climate Change Donations - Everett Jin; Ariya Shah; Hanyang Xia (Journal of Economics and Behavioral Studies, 2024)
Environmental non-profit organizations play a crucial role in fighting climate change. Most of them rely on donations from small donors whose donation decisions tend to be affected by personal factors. We examine the effects of behavioral factors on donations to climate change charities through a survey conducted among a group of participants with relatively homogenous demographic characteristics such as family wealth and educational background. We find that a potential donor’s donation amount is strongly affected by his or her perception of the effectiveness of environmental charities in fighting climate change. Among participants who pay more attention when filling out the survey, the persuasion tactic featuring factual information related to climate change appears to be most effective. Lastly, participants who feel good about having given to climate change charities are associated with larger donations, highlighting the effect of the psychological benefits of giving. Our study contributes to the behavioral economics literature by focusing on donors’ perspectives when examining the drivers behind charitable giving to climate change mitigation charities. Our findings suggest that climate charities should account for the effects of behavioral factors that best influence potential donors to improve fundraising success.